Pieces Framework for Analysis of User Saticfaction Internet of Things-Based Devices - Nestiara Lidya Kakihary (Universitas Bina Darma, 2021)
Internet of Things is a concept where internet connectivity can exchange information with one another with the existing devices around it. IoT can help humans in their daily activities. In general, Internet of Things-based devices can perform controlling and scheduling. In this research, an analysis of the level of power saving using smart lamp and smart plug devices based on the Internet of Things will be carried out. The analysis carried out in this study used the PIECES method which is a framework that can classify a problem, opportunity, and directives. Research on the efficiency of electricity savings based on IoT devices will be supported using devices and applications from Bardi Smart Home. In addition to the PIECES method, this analysis and research is supported by using the IoT framework: Conceptual Framework, and will be supported by IoT-based devices from Bardi Smart Home.